The Influence of Mobile Banking and Service Quality Toward Customers’ Saving Decision in Bank BRI Branch of Manna - Rio Aprian; Karona Cahya Susena; Tito Irwanto (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the influence of mobile banking and service quality toward customers’ saving decisions in Bank BRI Branch of Manna. The sample in this study was 97 customers of Britama savings in Bank BRI Branch of Manna. The sampling technique is accidental sampling technique. The data collection used a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed that Y = 11.723 +0.320X1 +0.423 X2, this illustrates a positive regression direction, meaning that there is a positive influence between X1 (Mobile Banking) and X2 (service quality) on customers’ saving decisions to (Y). It means that if the variables of Mobile Banking and service quality increase, it will increase the customer's saving decision. The magnitude of the coefficient of determination is 0.417. This means that X1 (Mobile Banking) and X2 (service quality) affect the customer's saving decision to (Y) by 41.7% while the remaining 58.3% is influenced by other variables not examined in this study. at a significance level of 0.05 explains that partially Mobile Banking variable and service quality have a significant influence toward customer's saving decision in Bank BRI Branch of Manna. F test results at a significance level of 0.05 explain that Mobile Banking variable and service quality have a simultaneous influence (together) on the customer's saving decision in Bank BRI Branch of Manna.